Uranium and arsenic bioremediation potential of plastic associated multi-metal tolerant Bacillus sp. EIKU23 - Atif Aziz Chowdhury; Nilendu Basak; Ekramul Islam (Journal of Hazardous Materials Letters)
Plastic waste accumulation is a significant environmental concern as it promotes microbial growth and acts as a carrier for heavy metals. This study focuses on a Bacillus sp. strain isolated from the surface of a used plastic bottle, tolerant to various potential toxic elements (PTEs) such as chromium, nickel, cobalt, copper, zinc, arsenite [As(III)], but sensitive to uranium (U) and arsenate [As(V)] toxicity. The strain demonstrates growth under different abiotic stress conditions, with the optimal pH range of 5.0–8.0 and a temperature of 30 °C. It shows remarkable removal capabilities, removing > 23.3% of U, > 38% of As(III)), and > 22.6% of As(V) from an initial dose of 100 mg L−1 in an aqueous solution. The biosorption capacity for U, As(III), and As(V) is 3.12, 3.1, and 1.8 mg g−1 of biomass, respectively. Kinetic modelling suggests that the biosorption of U and As(V) follows a pseudo-second-order mechanism, while As(III) biosorption follows a pseudo-first-order mechanism. Moreover, the strain has the ability to precipitate > 38.1% and ∼67% of U using bacterially released phosphate from inorganic and organic sources, respectively. These findings highlight the strain's potential for bioremediation of PTE-contaminated environments, providing valuable insights for optimizing metal removal and immobilization processes in future research.